Proteomic analysis of glycated proteins from streptozotocin-induced diabetic rat kidney - Chougale, Ashok D.; Bhat, Shweta P.; Bhujbal, Swapnil V.; Zambare, Mandar R.; Puntambekar, Shraddha; Somani, Rahul S.; Boppana, Ramanamurthy; Giri, Ashok P.; Kulkarni, Mahesh J. (Molecular Biotechnology, 2012)
Glycation of proteins leading to formation of advanced glycation end products (AGEs) has been considered as one of the important causes of diabetic nephropathy. Therefore, in this study, glycated proteins were detected by anti-AGE antibodies from kidney of streptozotocin-induced diabetic rat showing nephropathic symptoms, by using two dimensional electrophoresis and western blot analysis. These glycated proteins were identified and characterized by using combination of peptide mass finger printing and tandem mass spectrometric approaches. Glycated proteins identified included proteins from metabolic pathways, oxidative stress, cell signaling, and transport. Several of the proteins modified by glycation were involved in glucose metabolism. The extent of glycation was higher in diabetes compared to control, in the glycated proteins that were common to both control and diabetic kidney. Two dimensional electrophoresis proteins profiling of glycated proteins suggest that four of the glycated proteins were significantly up regulated in diabetes.
Keywords: AGE; Diabetes; Glucose toxicity; Nephropathy; Post-translation modification

Proteomic analysis of protease resistant proteins in the diabetic rat kidney - Bansode, Sneha B.; Chougale, Ashok D.; Joshi, Rakesh S.; Giri, Ashok P.; Bodhankar, Subhash L.; Harsulkar, Abhay M.; Kulkarni, Mahesh J. (Molecular & Cellular Proteomics, 2013)
Glycation induced protein aggregation has been implicated in the development of diabetic complications and neurodegenerative diseases. These aggregates are known to be resistant to proteolytic digestion. Here we report the identification of protease resistant proteins from the streptozotocin induced diabetic rat kidney, which included enzymes in glucose metabolism and stress response proteins. These protease resistant proteins were characterized to be advanced glycation end products modified and ubiquitinated by immunological and mass spectrometry analysis. Further, diabetic rat kidney exhibited significantly impaired proteasomal activity. The functional analysis of identified physiologically important enzymes showed that their activity was reduced in diabetic condition. Loss of functional activity of these proteins was compensated by enhanced gene expression. Aggregation prone regions were predicted by in silico analysis and compared with advanced glycation end products modification sites. These findings suggested that the accumulation of protein aggregates is an inevitable consequence of impaired proteasomal activity and protease resistance due to advanced glycation end products modification. Molecular & Cellular Proteomics 12: 10.1074/mcp.M112.020651, 228-236, 2013.

Proteomic study reveals downregulation of apolipoprotein A1 in plasma of poorly controlled diabetes: a pilot study - Bhonsle, Hemangi S.; Korwar, Arvind M.; Chougale, Ashok D.; Kote, Sachin S.; Dhande, Nitin L.; Shelgikar, Kishore M.; Kulkarni, Mahesh J. (Molecular Medicine Reports, 2013)
Proteomic approaches aid in gaining a better understanding of the pathophysiology of diabetic complications. In view of this, differential protein expression in diabetic plasma samples was studied by a combination of proteomic and western blot analyses. Diabetic plasma samples were categorized based on glycated haemoglobin levels as controlled diabetes (CD; 7-8%), poorly controlled diabetes (PCD; >8%) and non-diabetic control (ND;<6.4%). Two-dimensional electrophoresis and liquid chromatography-mass spectrometry revealed differential expression of proteins including upregulation of fibrinogen and haptoglobin and downregulation of vitamin D binding protein, alpha-1-antitrypsin, transthyretin and apolipoprotein A1 (Apo A1) in diabetic compared with non-diabetic plasma samples. Amongst these proteins, Apo A1 downregulation was prominent in PCD. Downregulation of Apo A1 may serve as an early predictive marker of diabetic complications.
Keywords: biomarker; HbA1c; proteomics